Nature's network - Reid, Keith; American Museum of Natural History (London : Published for thAldus Books, 1969)
Describes how animals and plants interact to help preserve, directly or indirectly, each others life cycles.
Includes index.
Keywords: Ecology -- Juvenile literature; Ecology